2022
DOI: 10.1083/jcb.202106092
|View full text |Cite
|
Sign up to set email alerts
|

Filament organization of the bacterial actin MreB is dependent on the nucleotide state

Abstract: MreB, the bacterial ancestor of eukaryotic actin, is responsible for shape in most rod-shaped bacteria. Despite belonging to the actin family, the relevance of nucleotide-driven polymerization dynamics for MreB function is unclear. Here, we provide insights into the effect of nucleotide state on membrane binding of Spiroplasma citri MreB5 (ScMreB5). Filaments of ScMreB5WT and an ATPase-deficient mutant, ScMreB5E134A, assemble independently of the nucleotide state. However, capture of the filament dynamics reve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(62 citation statements)
references
References 73 publications
(131 reference statements)
5
41
0
Order By: Relevance
“…The P i release rate constant was 1.5 ± 0.2 nM (P i )/s/μM (protein), as estimated from the linear-fit slope of SpeMreB5 concentration-dependent P i release rates ( figure 3 c ). This value is consistent with those of SciMreB5, TmMreB, EcMreB and actin (electronic supplementary material, table S2) [ 5 , 38 , 40 42 ]. However, the P i release of SpeMreB3 was too slow to estimate the rate constant, even at 10 µM ( figure 3 a–c ; electronic supplementary material, table S2), a concentration at which we observed filaments using EM ( figure 1 a ; electronic supplementary material, figure S3C and D).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The P i release rate constant was 1.5 ± 0.2 nM (P i )/s/μM (protein), as estimated from the linear-fit slope of SpeMreB5 concentration-dependent P i release rates ( figure 3 c ). This value is consistent with those of SciMreB5, TmMreB, EcMreB and actin (electronic supplementary material, table S2) [ 5 , 38 , 40 42 ]. However, the P i release of SpeMreB3 was too slow to estimate the rate constant, even at 10 µM ( figure 3 a–c ; electronic supplementary material, table S2), a concentration at which we observed filaments using EM ( figure 1 a ; electronic supplementary material, figure S3C and D).…”
Section: Resultssupporting
confidence: 89%
“…In contrast to our model, the ATP hydrolysis-deficient variants used in this study except for SpeMreB3 S176D showed lower or similar critical concentrations compared with the corresponding wild-types ( figure 4 c ; table 1 ). This result may be caused by subtle differences in active site structures between the variants and the corresponding wild-types, which can change the overall conformation, thereby leading to different polymerization ability [ 4 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that Fibril supports propagation of kinks necessary for Spiroplasma movement by potentially transmitting the force generated by itself and MreBs to the membrane ( Kiyama et al., 2021 ; Lartigue et al., 2021 ). Force generation could arise due to the ATP hydrolysis activity of MreBs ( Pande et al., 2022 ; Sasajima and Miyata, 2021 ). Further studies are required to understand whether the conformational changes in Fibril, if any, and its interaction with MreBs ( Harne et al., 2020a ) are necessary for generating or relaying the force.…”
Section: Introductionmentioning
confidence: 99%
“…The tendency to aggregation upon purification hampered most in vitro studies of MreBs from other species (Dersch et al , 2020; Gaballah et al , 2011; Mayer & Amann, 2009). More recently, MreBs from several G- bacteria and from the wall-less bacterium Spiroplasma citri (MreB5 Sc ) could be purified in a functional soluble form, albeit in much lower quantities than MreB Tm (Harne et al , 2020; Maeda et al , 2012; Nurse & Marians, 2013; Pande et al , 2022; Salje et al ., 2011; van den Ent et al , 2014). Direct binding to the cell membrane was shown for MreB from the G- Escherichia coli and T. maritima (Salje et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The directionality and the kinetics of MreB polymerization, as well as the role of nucleotides in this process remain to be shown. ATPase activity has been reported in solution for MreB Tm , MreB Ec and, more recently, for MreB5 Sc (Esue et al ., 2005; Esue et al ., 2006; Nurse & Marians, 2013; Pande et al ., 2022; Popp et al ., 2010b). However, the need for nucleotide binding and hydrolysis in polymerization remains unclear due to conflicting results, in vivo and in vitro , including the ability of MreB to polymerize or not in the presence of ADP or the non-hydrolysable ATP analogue AMP-PNP (adenylyl-imidodiphosphate).…”
Section: Introductionmentioning
confidence: 99%